Efektivitas Model Pembelajaran Problem Based Learning Pada Mata Pelajaran Dasar Ketenagalistrikan Di SMK Negeri 1 Sumatera Barat - Syopian Siregar Dongoran; Sukardi (Journal of Electrical Vocational Education, 2025)
This study aims to determine the effectiveness of the Problem Based Learning (PBL) learning model on student learning outcomes in the Basic Electrical Power Subject at SMK Negeri 1 West Sumatra. This study uses a quantitative approach with a quasi-experimental method and a non-equivalent control group design. The subjects of this study consisted of two classes, namely class X TITL 2 as the experimental class and class X TITL 1 as the control class, each consisting of 36 students. The research instrument used was a multiple-choice test that had been tested for validity and reliability. Data collection techniques were carried out through the administration of pretests and posttests. Data were analyzed using the Independent Sample t-test to determine differences in learning outcomes between the two groups. The results showed that the average posttest score of the experimental class was 82.18, while the control class was 66.91. The results of the hypothesis test showed a significance value of 0.000 <0.05, so there was a significant difference between the two groups. Thus, it can be concluded that the Problem Based Learning learning model is effective in improving student learning outcomes in the Basic Electricity subject.